TAXONOMY OF LEARNING OBJECTIVES - Harahap, Yudi Septian; Sya'bana, Dzul Fadhli; Nurhaliza, Siti; Nurmawati, Nurmawati (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
Taxonomy of Learning Objectives is a concept used to describe a hierarchical structure in understanding learning objectives. This concept divides the learning objectives into different levels, which include knowledge, understanding, application, analysis, evaluation, and creation. The importance of the taxonomy of learning objectives in supporting an effective learning process. This taxonomy provides a structured framework for developing curricula, designing learning experiences, and evaluating student achievement. The purpose of this study To formulate training objectives, the use of a Training Taxonomy is necessary. Taxonomy is a tool that classifies and shows the relationship between various elements. One form of taxonomy is used to determine learning objectives and consider learning outcomes. As such, this abstract highlights the importance of a taxonomy of learning objectives in helping achieve effective learning and comprehensive cognitive development for students.